1989
DOI: 10.1051/forest:19890206
|View full text |Cite
|
Sign up to set email alerts
|

Dynamique de l'eau dans une chênaie (Quercus petraea (Matt.) Liebl.) en forêt de Fontainebleau

Abstract: Throughfall, interception and stemflow for three years were 70.6-28.8 and 0.6 per cent of gross precipitation (average value over 3 years) respectively, while those in nonfoliated conditions : 76.6, 22.4, 1.0% of Pi in foliated conditions : 65.5, 34.4, 0.1 % of Pi; transpiration was of 76.4% of Pi (T = 288.4 mmlyear). During the growing seasons T/ETP ratio is related to the evolution of the stomatal resistance with leaf age (at maximal leaf area index and negligible soil-water stress, TlETP increases in spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…This corresponds also to the recent study of Martin et al [25], who demonstrated that an infinite surface conductance (representing wet leaf surfaces) would increase forest evaporation severalfold under a given radiation input. The observed amount for E i of 16 % of P G for beech and alder forest is even lower than the 29 % reported by Nizinski and Saugier [29] for the above-mentioned oak forest of Fontainebleau, but matches a range that is typical for broadleaved forests in temperate regions [18,30].…”
Section: The Alder Standmentioning
confidence: 40%
See 1 more Smart Citation
“…This corresponds also to the recent study of Martin et al [25], who demonstrated that an infinite surface conductance (representing wet leaf surfaces) would increase forest evaporation severalfold under a given radiation input. The observed amount for E i of 16 % of P G for beech and alder forest is even lower than the 29 % reported by Nizinski and Saugier [29] for the above-mentioned oak forest of Fontainebleau, but matches a range that is typical for broadleaved forests in temperate regions [18,30].…”
Section: The Alder Standmentioning
confidence: 40%
“…Whilst some authors explicitly set this component of the forest water balance to zero [29,31,42], others put emphasis on the significant amount of soil evaporation even under a closed forest canopy [41], especially under wet climatic conditions. Kelliher et al [19] reported that 10-20 % of the total evaporation in a closed Nothofagus forest came from the soil surface.…”
Section: The Alder Standmentioning
confidence: 99%
“…Hence, it is suggested that Calder et al (2002) over predict evapotranspiration and under predict interception. The question addressed in this paper is to determine the reasons why Calder et al (2002) found such dissimilar results as compared to Nizinski and Saugier (1989).…”
Section: Introductionmentioning
confidence: 99%
“…Calder et al (2002) also optimised the winter interception parameters and found that interception was equal to 18% of the annual rainfall. However, Nizinski and Saugier (1989) measured oak interception and found it to be equal to 25%. Hence, it is suggested that Calder et al (2002) over predict evapotranspiration and under predict interception.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation